Conceptual and Contextual Perspectives on the Modern Law of Treaties - Bowman, Michael J. (Cambridge University Press, 2018)
An innovative volume of essays contrasting conceptual and contextual approaches to the modern law of treaties
Description based on publisher supplied metadata and other sources
Keywords: International obligations; International organization; Treaties; Internationale Politik; Internationales Vertragsrecht; Aufsatzsammlung